Solve the following inequality: 2(x 1) – (–x 5) ≤ –18
2 answers:
I hope this is correct
Simplifying (2x + -1)(x + -3) = 18 Reorder the terms: (-1 + 2x)(x + -3) = 18 Reorder the terms: (-1 + 2x)(-3 + x) = 18 Multiply (-1 + 2x) * (-3 + x) (-1(-3 + x) + 2x * (-3 + x)) = 18 ((-3 * -1 + x * -1) + 2x * (-3 + x)) = 18 ((3 + -1x) + 2x * (-3 + x)) = 18 (3 + -1x + (-3 * 2x + x * 2x)) = 18 (3 + -1x + (-6x + 2x2)) = 18 Combine like terms: -1x + -6x = -7x (3 + -7x + 2x2) = 18 Solving 3 + -7x + 2x2 = 18 Solving for variable 'x'. Reorder the terms: 3 + -18 + -7x + 2x2 = 18 + -18 Combine like terms: 3 + -18 = -15 -15 + -7x + 2x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -15 + -7x + 2x2 = 0 Factor a trinomial. (-3 + -2x)(5 + -1x) = 0
Answer:
x<=-7
Step-by-step explanation:
2(x- 1) – (–x- 5) ≤ –18
Open the bracket
2x -2+x+5<= -18
3x +3<= -18
Then we will collect the like term
All the x variable should be on the left hand side and all the constant should be on the right hand side
Thus;
3x<=-18-3
3x<= -21
Divide both side of the equation by the coefficient of x
3x/3 <= -21/3
X <= -7
You might be interested in
V= piR^2(h)
6283=pi(10^2)(h)
6283=pi(100)h
height = 6283/(pi(100))
then round to the nearest inch
Answer:
you would get about 6:20 of sleep
.75x +1.29 = 7.00
x = the amount of bagels he wants.
Let's use tenths.
1/10 = 0.10
5/10 = 0.50
<span>1/10 + 5/10 = 6/10 = 0.6</span>
Answer:
f(x)=-2x+9 g(x)=-4x^2+5x-3Now, f o g (x) = f{g(x)} = f(4x^2+5x-3) = 2(4x^2+5x-3) + 9 = 8x^2+10x-6 + 9
Step-by-step explanation: